The Complexity of the ERK/MAP-Kinase Pathway and the Treatment of Melanoma Skin Cancer - Wellbrock, Claudia; Arozarena, Imanol (Frontiers in Cell and Developmental Biology, 2016)
The central role played by the ERK/MAPK pathway downstream of RAS in human neoplasias is best exemplified in the context of melanoma skin cancer. Signalling through the MAPK pathway is crucial for the proliferation of melanocytes, the healthy pigment cells that give rise to melanoma. However, hyper-activation of the MAPK-pathway is found in over 90% of melanomas with approximately 50% of all patients displaying mutations in the kinase BRAF, and approximately 28% of all patients harbouring mutations in the MAPK-pathway up-stream regulator NRAS. This finding has led to the development of BRAF and MEK inhibitors whose application in the clinic has shown unprecedented survival responses. Unfortunately the responses to MAPK pathway inhibitors are transient with most patients progressing within a year and a median progression free survival of 7-10 months. The disease progression is due to the development of drug-resistance based on various mechanisms, many of them involving a rewiring of the MAPK pathway. In this article we will review the complexity of MAPK signalling in melanocytic cells as well as the mechanisms of action of different MAPK-pathway inhibitors and their correlation with clinical response. We will reflect on mechanisms of innate and acquired resistance that limit patient’s response, with a focus on the MAPK signalling network. Because of the resurgence of antibody-based immune-therapies there is a growing feeling of failure in the targeted therapy camp. However, recent studies have revealed new windows of therapeutic opportunity for melanoma sufferers treated with drugs targeting the MAPK pathway, and these opportunities will be discussed.